Cut it out! Thoracic surgeon's approach to pulmonary mucormycosis and the role of surgical resection in survival. Issue 10 (6th August 2019) - Multani, Ashrit; Reveron‐Thornton, Rosyli; Garvert, Donn W.; Gomez, Carlos A.; Montoya, Jose G.; Lui, Natalie S.
Summary: Background: Mucormycosis portends a poor prognosis with mortality rates ranging from 50% to 70% in pulmonary mucormycosis (PM) and up to 95% in disseminated disease. However, detailed outcomes data have been lacking. It remains unknown how to identify patients who would benefit from surgical resection. Objectives: We present our experience with patients undergoing surgical resection for PM, including an analysis of factors affecting postoperative survival. We also describe a thoracic surgeon's approach through illustrative cases. Patients/Methods: We conducted a single‐centre retrospective study of all adult patients with PM who received antifungal therapy and underwent surgical resection or who received antifungal therapy alone at Stanford between January 2004 and June 2018. Results: Twelve patients received antifungal therapy and underwent surgical resection and 13 patients received antifungal therapy alone. From infection onset to death (or right‐censoring if still alive), patients who underwent surgical resection had a median survival of 406 days (mean, 561.3; range, 22‐2510), and patients who received antifungal therapy alone had a median survival of 28 days (mean, 66.7; range, 8‐447). In patients who underwent surgical resection, median postoperative survival time was 154 days (range, 11‐2495), in‐hospital mortality was 16.7%, and 1‐year mortality was 50.0%. Age, primary disease, ASA status, extrapulmonary dissemination, laterality, multilobar involvement, number of lesions, largest lesion size, platelet count, surgical approach, type of resection or extent of resection were not significantly associated with postoperative survival. Conclusions: Surgical resection significantly increases survival and should be strongly considered for selected patients with PM.